Increased susceptibility to oral Trichuris muris infection in the specific absence of CXCR5+ CD11c+ cells. (13th July 2018) - Bradford, Barry M.; Donaldson, David S.; Forman, Ruth; Else, Kathryn J.; Mabbott, Neil A.
Summary: Trichuris muris is a natural mouse helminth pathogen which establishes infection specifically in the caecum and proximal colon. The rapid expulsion of T. muris in resistant mouse strains is associated with the induction of a protective T helper cell type 2 (Th2)‐polarized immune response. Susceptible mouse strains, in contrast, mount an inappropriate Th1 response to T. muris infection. Expression of the chemokine CXCL13 by stromal follicular dendritic cells attracts CXCR5‐expressing cells towards the B‐cell follicles. Previous studies using a complex in vivo depletion model have suggested that CXCR5‐expressing conventional dendritic cells (cDC) help regulate the induction of Th2‐polarized responses. Here, transgenic mice with CXCR5 deficiency specifically restricted to CD11c + cells were used to determine whether the specific absence CXCR5 on CD11c + cells such as cDC would influence susceptibility to oral T. muris infection by affecting the Th1/Th2 balance. We show that in contrast to control mice, those which lacked CXCR5 expression on CD11c + cells failed to clear T. muris infection and developed cytokine and antibody responses that suggested a disturbed Th1/Th2 balance with enhanced IFN‐γ expression. These data suggest an important role of CXCR5‐expressing CD11c + cells such as cDC in immunity to oral T. muris infection.